‘It builds on trust’: Exploring fishers’ trust in management of fisheries in Norway - Crosman, Katherine M.; Hayes, Adam L. (Frontiers in Marine Science, 2025)
This paper explores trust in fishery management in Norway, reporting results from a survey (n=184) of Norwegian coastal cod and herring fishers. We explore antecedents of trust identified in prior literature, including dispositional trust and perceptions of managers, as well as characteristics of management data, using factor analysis. We use the resulting factors, combined with other potential influences on trust (demographic variables, self-reported understanding of management, and stakes) to predict a) trust in Norwegian fisheries management in general and b) trust in management of a relatively novel, controversial fishery for Calanus finmarchicus. We supplement the statistical approach with analysis of open-ended survey responses asking respondents to explain their trust judgements. We find that the antecedents of trust derived from prior work load onto three distinct factors, representing data quality, perceived manager benevolence, and salient value similarity. Respondents also mentioned each of these antecedents of trust in their open-ended responses; a significant minority also mentioned perceived management bias. Respondents who reported higher trust in management generally referenced different concepts in their justifications (e.g., research) than those who reported lower trust (e.g., the management agency). Our model results show that these three antecedents of trust are positively and significantly predictive of probable trust in general fisheries management. However, the antecedents of trust are much less predictive for trust in Calanus management. Resource users' trust in management is commonly forwarded as a key component in successful, sustainable management of natural resources. Norway is generally perceived to be a high trust society, but our results indicate that low trust in Calanus management is a function of more than simply known trust antecedents.